Atualidade de Paulo Freire - Balduino Antonio Andreola; Gomercindo Ghiggi (Educação Online, 2013)
Resumo advindo do próprio trabalho: "A atualidade de Paulo Freire pode ser avaliada a partir de diferentes indicadores, entre eles, o das instituições, no Brasil e no mundo, dos grupos e movimentos que promovem pesquisas, ações e projetos, nos campos da educação e desenvolvimento humano em geral. No Rio Grande do Sul, a XV sessão anual do Fórum de Estudos: Leituras de Paulo Freire, realizada em 2013, teve mais de duzentos trabalhos apresentados. O VIII Colóquio Internacional do Centro Paulo Freire de Estudos e Pesquisas, de Recife, teve participação ainda mais ampla. O Instituto Paulo Freire de São Paulo, é outro exemplo da atualidade do autor. Pedagogia do oprimido, tem hoje 50 edições e está traduzido em mais de 20 línguas, Educação como prática da liberdade está na 34ª edição e Pedagogia da autonomia, na 43ª. Pedagogia do oprimido é mais que um livro, um projeto a serviço de um mundo mais solidário, e foi recriado de muitas maneiras, no mundo inteiro, nos campos da educação, da ética, da ecologia, da saúde, da cultura e da política."

Summary coming from the work itself: "The timeless of Paulo Freire can be evaluated from different indicators. One of them, the institutions in Brazil and over the world, of groups and movements that promote research, actions and projects in the fields of education and human development in general. In Rio Grande do Sul, the Forum of Studies: Readings of Paulo Freire, hosted each year by a different institution of higher education, held in 2013 its XV annual session with the presentation of over two hundred works. The VIII International Colloquium at Paulo Freire Center of Studies and Research of Recife took place this year with a much broader participation. The Instituto Paulo Freire of São Paulo, with a wide range of promotions and publications, is another example among us of the timeless of Freire. With regard to the dissemination of his works in Brazil, we just remember the number of editions of four of his books: 50 of Pedagogy of the oppressed, 34 of Education as practice of freedom, 34 of Education and change, and 43 of Pedagogy of autonomy. Pedagogy of the oppressed is translated into more than twenty languages. Roger Pedagogy of the oppressed is not a book, it is a project in the service of a more caring world and, as such, recreated in many ways, by thousands of educators and millions of people throughout the world, in the fields of education, ethics, ecology, health, culture and politics, as he has written that we must "reinvent the power"."
Paulo Freire Timeless
Keywords: Educação; Ecologia; Ética; Libertação; Universalidade; Reconhecimento mundial; Education; Ecology; Ethics; Liberation; Universality; Worldwide recognition